Implementasi Good University Governance Dalam Meningkatkan Mutu Pendidikan Tinggi: Sebuah Systematic Literature Review - Puspitasari, Ria; Rodiyah, Sinta; Kholid, Idham; Yuniar, Yuniar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine in depth the implementation of Good University Governance and its contribution to improving the quality of higher education. The research employs a Systematic Literature Review method with data sourced from journal articles published in the last five years. Data collection techniques include literature selection, extraction, and synthesis, while data analysis is carried out using thematic analysis and concept mapping. The synthesis results show that the implementation of GUG has a positive impact on improving accreditation, managerial performance, the quality of academic services, and stakeholder trust when supported by Internal Quality Assurance mechanisms, periodic audits, and the use of digital governance to strengthen information transparency and data-driven decision-making. Nevertheless, many institutions still face implementation challenges such as bureaucratic organizational culture, limited human resource capacity, weak institutional independence, and dependence on government regulations that frequently change.This SLR also confirms that the most effective implementation model is a hybrid model that integrates IQA, shared governance, and digital information systems holistically.